2017
DOI: 10.22571/actabra12201735
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resistances of gastrointestinal nematodes to anthelmintic groups in cattle of semiarid of Paraíba, Brazil

Abstract: The purpose of this research was to test the main anthelmintic drugs, such as Avermectins, Benzimidazoles, Imidazothiazoles, Tetrahydropyrimidines and Salicylanilides, used for the control of gastrointestinal nematodes in bovines on cattle ranches in the semiarid region of the state of Paraíba, Brazil. This study involved 40 animals per ranch, making a total of 200 animals of mixed breeds, varying in age from 12 to 36 months, with eggs per gram of faeces (EPG) >500. The anthelmintics were administered to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Resistance to closantel was observed on 75% (15/20) of the farms, with 55.8% of efficacious mean for FECR, which was similar to the results obtained by Ramos et al (2020), of 55.2%, and Silva et al (2017), of 45.45%. However, Bushra et al (2019) and Maqbool et al (2018) found reductions of 94.44% and 100%, respectively, in India.…”
Section: Farmsupporting
confidence: 83%
See 3 more Smart Citations
“…Resistance to closantel was observed on 75% (15/20) of the farms, with 55.8% of efficacious mean for FECR, which was similar to the results obtained by Ramos et al (2020), of 55.2%, and Silva et al (2017), of 45.45%. However, Bushra et al (2019) and Maqbool et al (2018) found reductions of 94.44% and 100%, respectively, in India.…”
Section: Farmsupporting
confidence: 83%
“…The Haemonchus was the most prevalent parasite genus in all larval cultures, both before and after treatments. This has also been reported in several other studies evaluating bovine gastrointestinal nematodes (Borges et al, 2015;Lobayan et al, 2017;Silva et al, 2017;Ramos et al, 2020). This nematode probably acquires resistance faster due to its high biotic potential and great genetic variability.…”
Section: Farmsupporting
confidence: 78%
See 2 more Smart Citations
“…In tropical countries, the genera Haemonchus, Cooperia, Trichostrongylus, and Oesophagostomum are the most prevalent GIN in domestic ruminants, causing problems to animal health [55][56][57][58]. In horses, small strongyls (cyathostomins) and large strongyls (Strongylus spp.)…”
Section: Advances In the Control Of Gastrointestinal Nematodes In Pasture Animalsmentioning
confidence: 99%